Entrepreneurial Passion and Personality: The Case of Academic Entrepreneurship - Obschonka, Martin; Moeller, Julia; Goethner, Maximilian (Frontiers in Psychology, 2019)
Since entrepreneurial thinking and acting within organizations is increasingly important for the success of organizations, entrepreneurial passion is an emerging key construct in the study of organizational behavior. Here we quantify effects of personality traits on entrepreneurial passion in organizations, thereby comparing a person- vs. variable-oriented trait approach and testing such effects against alternative explanation models (rational choice approach, social learning approach, and social identity approach). Analyzing data from N = 137 German scientists across two measurement occasions, structural equation modeling revealed that an entrepreneurial Big Five profile (person-oriented approach), but none of the single Big Five traits (variable-oriented approach), predicted entrepreneurial passion (which in turn mediated the link between this domain-specific personality profile and entrepreneurial behavior). Likewise, the entrepreneurial personality profile, but not the single Big Five traits, predicted the simultaneous occurrence of entrepreneurial passion and behavior (passionate entrepreneurial behavior). Interestingly, the alternative explanation models (rational choice approach, social learning approach, and social identity approach) failed to predict entrepreneurial passion and passionate entrepreneurial behavior. The results suggest that the basic entrepreneurial personality character of a person contributes to the shaping of his or her entrepreneurial passion, which is relevant for actual entrepreneurial activity. The results thus illustrate how a person-oriented trait approach can inform the study, and concepts of, entrepreneurial passion.